Determinants of effective perfotmance of the livestock sector in Nigeria - ODII, M A C A; OFIABULU, E C (The Indian Journal of Animal Sciences, 2014)
The macroeconomic variables performance of the livestock industry in Nigeria were studied. Multiple regression analysis revealed that price variable has negative impact on livestock output, exchange rate and interest rate variable have significant positive effect on output of poultry while money supply has no effect on swine output. Also macroeconomic indication such as gross domestic product, exchange rate and domestic production significantly influence livestock import demand. The study recommended awong others, proper care and recognition of the different macroeconomic policy variables that have shown positive and significant influence in the performance of the livestock sector. Negative and nonsignificant factors should be de-emphasised.